Molecular cloning of the Pseudomonas carboxypeptidase G2 gene and its expression in Escherichia coli and Pseudomonas putida. - Minton, N P (1983)
The gene coding for carboxypeptidase G2 was cloned from Pseudomonas sp. strain RS-16 into Escherichia coli W5445 by inserting Sau3A-generated DNA fragments into the BamHI site of pBR322. The plasmid isolated, pNM1, was restriction mapped, and the position of the gene on the 5.8-megadalton insert was pinpointed by subcloning. The expression of carboxypeptidase in E. coli was 100-fold lower than in the Pseudomonas sp. strain. When the cloned gene was subcloned into the Pseudomonas vector pKT230 and introduced into Pseudomonas putida 2440, a 30-fold increase in expression over that obtained in E. coli was observed. High expression (up to 5% soluble protein) was obtained in E. coli by subcloning a 3.1-megadalton Bg/II fragment into the BamHI site of pAT153. The increased expression was orientation dependent and is presumed to be due to transcriptional readthrough from the Tc promoter of the vector. Production of carboxypeptidase was shown to be induced (two-fold) by the presence of folic acid, and the mature protein was shown to be located in the periplasmic space of E. coli.